Methodological Approach for Optimizing Production of Oxygen by Adsorption of Nitrogen from Air using Zeolite Li-LSX - Marwa Al-Yousuf; Raghad F. Almilly; Riyadh Kamil (International Journal of Chemical Engineering)
This research investigates the optimum operating conditions related to the adsorption of nitrogen gas from ambient air on zeolite Li-LSX to produce oxygen gas by the pressure-vacuum swing adsorption process. Experiments were performed using a column (4 cm inside diameter and 17 cm length) packed with different heights of packing (h) of zeolite (9, 12, and 16 cm) from 0.4 to 0.8 mm diameter pellets. At each packing height, different flow rates (f) (2, 4, 6, 8, and 10 L·min−1) for different input pressures (p) (0.5, 1, 1.5, 2, and 2.5 bar) were used to detect their effects on the purity of produced oxygen as percentage volume of the outlet air stream. The results showed that the purity of produced oxygen increased with increasing packing height, pressure, and flowrate to a specific limit. The maximum purity obtained was 73.15% at 16 cm packing height, 2.5 bar input pressure, and 6 L·min−1 inlet flowrate, and the productivity was equal to 18 mmol·(Kg·s)−1 at these conditions. A response surface methodology was used to determine the most influential variables and their interactions. The results confirmed the strong effects of the input pressure, the packing height, and to a lesser extent, the flowrate. A quadratic model was predicted based on the experimental result and assessed statistically. The impacts of quadratic terms in the model were in the order: of p∗p>p∗h>p∗f. The model was applied to predict the operating conditions of 95% purity of oxygen.